The role of a mass media campaign in uptake of HIV counselling and testing among young people in five Southern Africa countries - Kamugisha, Leonard (My University, 2018)
Introduction Southern Africa forms the epicentre of the HIV epidemic and young people commonly get diagnosed long after infection. Despite the evidence that HIV Counselling and Testing (HCT) can reduce risky sexual behaviors and prevent HIV, uptake of testing in young people remains limited and this is especially true in Southern Africa. In the last few years, effective interventions for HIV prevention have been implemented, including treatment as prevention and pre-exposure prophylaxis. In the context of very high prevalence of HIV among young people in Southern Africa, it is critical that countries attain higher levels of HCT. Demand creation is one of the means to increase uptake of HCT. This study investigated the relationship between exposure to a mass media campaign and uptake of HIV counselling and testing among young people in five countries of Southern Africa (Lesotho, Mozambique, South Africa, Swaziland and Zambia) for the period 2008 to 2012. A secondary data analysis from a multi-country study was undertaken. Methods: Secondary data on young people aged 15-24 years from a post-only cross-sectional observational multi-country study that was undertaken in 2012 to evaluate the One Love Campaign, a regional behavior change media campaign coordinated by Soul City Institute for Development Communication was undertaken. The exposure variable was exposure to One Love campaign (in the form of television film series; locally produced radio drama series, television public service announcements and a television series in South Africa. In other participating countries the programme also comprised talk shows broadcast by national- and community broadcasters; booklets, billboards used to trigger discussion during community dialogues and community outreach events) with the outcome of interest being HIV testing, with a number of covariates such as socio-demographic characteristics (e.g age, education level, nationality, sex, marital status, socio-economic status (defined as wealth quintile), whether respondent had children or not, and country of residence. Bivariate and multivariate analysis was conducted to establish the relationship between exposure to One Love campaign and HIV testing among the study population. Results: A total of eight-thousand-six-hundred and thirteen young people (n=8613) participated in the study. There was nearly equal distribution of respondents between those that had had an HIV test (52.0%) and those that had not (48.0%). Exposure to One Love through multiple media, was positively associated with HIV testing (aOR=2.34, 95% CI 1.94-2.81), and there was a dose response. Other factors associated with having an HIV test included being female (aOR= 1.95, 95% CI 1.75 - 2.18); having living child (aOR=4.23, 95% CI 3.57-5.01); being the aged 18-20 years (aOR=2.24, 95% CI 1.95 - 2.58) or group 20-24 years (aOR=4.14, 95% CI 3.57 - 4.81) and having secondary or tertiary education ( aOR= 2.67, 95% CI 1.92 - 3.68). Increased wealth until quintile 4 was negatively associated with having an HIV test, (aOR= 0.93, 95% CI 0.77 - 1.12). Conclusion: Overall the findings of this study show that exposure to more than one medium in the campaign has greater odds of testing. The results of this study provide important information on the relationship between exposure to a media campaign and HIV testing among young people. Social and behaviour change communication strategies that use multi-media are necessary to achieve improved HIV testing among young people.
A research report submitted to the School of Public Health, University of the Witwatersrand in partial fulfillment of the requirements for the degree of Master of Public Health. June 2018.
Keywords: HIV Counselling and Testing; HIV